Can an ethics code help to achieve equity in international research collaborations? Implementing the global code of conduct for research in resource-poor settings in India and Pakistan. (October 2022) - Chatfield, Kate; Lightbody, Catherine Elizabeth; Qayum, Iftikhar; Ohly, Heather; Rasgado, Marena Ceballos; Watkins, Caroline; Lowe, Nicola M
The Global Code of Conduct for Research in Resource-Poor Settings (GCC) aims to stop the export of unethical research practices from higher to lower income settings. Launched in 2018, the GCC was immediately adopted by European Commission funding streams for application in research that is situated in lower and lower-middle income countries. Other institutions soon followed suit. This article reports on the application of the GCC in two of the first UK-funded projects to implement this new code, one situated in India and one in Pakistan. Through systematic ethics evaluation of both projects, the practical application of the GCC in real-world environments was tested. The findings of this ethics evaluation suggest that while there are challenges for implementation, application of the GCC can promote equity in international research collaborations.